Current Occupational Perspective of Total Hip Joint Surgeons in China: A Survey of Members of the Chinese Orthopedic Association. Issue 9 (1st August 2022) - Kong, Ning; Tian, Run; Cao, Li; Zhou, Yonggang; Wang, Kunzheng; Yang, Pei
Abstract : Objectives: To explore the basic occupational information and the preferences of surgical techniques in Chinese joint surgeons. Methods: A survey study was conducted during the Chinese Hip Society (CHS) conference of 2020. Participants from hospitals all over the country were included as the potential respondents. The questions were asked for respondents' basic information, overviews of total hip arthroplasty (THA), surgical techniques, and prosthesis selection. After data collection and filtration, analysis was conducted using chi‐square test or Fisher's exact test. Results: Only 8.31% of joint surgeons used robotics or navigation systems to assisted their total hip arthroplasty. For the approach preference, posterolateral approaches were generally favored, being used commonly by 75.36% of respondents while the direct anterior approach was considered the preferred choice by 8.31% of Chinese joint surgeons. 24.36% of the respondents choose to use domestic prosthesis in over 80% of their patients. Conclusions: The intelligent THA is in the early stage at present but developing rapidly in China. The composition of surgical approach is simple at present and the continuing education should aim at increasing the diversity of approach selection in the following years. Domestic prosthesis is playing significant role in the prosthesis market. Joint registration system is urgently needed for Chinese joint surgery. Abstract : The posterolateral approach is favored by most Chinese hip joint surgeons while the direct anterior approach is becoming popular. The use of robot or navigation assistance in total hip joint surgery is promising. A multi‐functional joint registration system is an urgent need to have a better understanding of Chinese orthopedics.